Nietzsche: Bipolar Disorder and Creativity - Cybulska, Eva M. (The Indo-Pacific journal of phenomenology, 2019)
This essay, the last in a series, focuses on the relationship between Nietzsche's mental illness and his philosophical art. It is predicated upon my original diagnosis of his mental condition as bipolar affective disorder, which began in early adulthood and continued throughout his creative life. The kaleidoscopic mood shifts allowed him to see things from different perspectives and may have imbued his writings with passion rarely encountered in philosophical texts. At times hovering on the verge of psychosis, Nietzsche was able to gain access to unconscious images and the music of language, usually inhibited by the conscious mind. He reached many of his linguistic, psychological and philosophical insights by willing suspension of the rational. None of these, however, could have been communicated had he not tamed the subterranean psychic forces with his impressive discipline and hard work.